Gender differences in the response to resistance training in cardiac patients - Sika, Rulla (My University, 2010)
Women often have reduced self-efficacy for physical activity and particularly for activities that require muscular strength. It is unclear whether normal cardiac rehabilitation programs, which have only minimal resistance training, adequately treat this deficit in self-efficacy. The purpose of this study is to observe changes in self-efficacy in male and female patients across the duration of a cardiac rehabilitation program. Male and female patients enrolled in a Phase II rehabilitation program were assessed for self-efficacy for activities involving walking distance, lifting, carrying, holding and common household tasks near the beginning, mid-point and end of their individually tailored program. The main finding of this study is that women have lower self-efficacy scores prior to and throughout CR. Both genders improved at the same rate with no interaction. Men finished above the arbitrary 85% value for expected self-efficacy for the overall self-efficacy, lifting, carrying, and holding scores while women were below the 85% value for all activities.
Keywords: Self-efficacy; Isometric exercise; Heart -- Diseases -- Patients -- Rehabilitation -- Sex differences